1984
DOI: 10.1177/153857448401800409
|View full text |Cite
|
Sign up to set email alerts
|

Superficial Temporal Artery To Middle Cerebral Artery Anastomoses in the Sylvian Fissure: Case Report

Abstract: An anastomosis between the superficial temporal artery (STA) and the superior trunk of division of the middle cerebral artery (MCA) resulted in significant clinical improvement and normalization of the impaired cerebral blood flow. Possible indications for this type of anastomosis and microanatomical data from the proximal MCA are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Gibo et al described a patient who had both a duplicated and an accessory MCA in which the duplicated artery was distributed to the temporopolar, anterior, and middle temporal areas 23. Umansky et al reported a case in which the main MCA irrigated the frontal and parietal lobes, while the duplicated MCA provide blood supply to the temporal lobe 10 , 11. Komiyama et al affirmed that the DMCA consistently reached the temporopolar, as well as the anterior and/or middle temporal territories 20.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gibo et al described a patient who had both a duplicated and an accessory MCA in which the duplicated artery was distributed to the temporopolar, anterior, and middle temporal areas 23. Umansky et al reported a case in which the main MCA irrigated the frontal and parietal lobes, while the duplicated MCA provide blood supply to the temporal lobe 10 , 11. Komiyama et al affirmed that the DMCA consistently reached the temporopolar, as well as the anterior and/or middle temporal territories 20.…”
Section: Discussionmentioning
confidence: 99%
“…Komiyama et al affirmed that the DMCA consistently reached the temporopolar, as well as the anterior and/or middle temporal territories 20. Hence, the cortical areas supplied by the DMCA are similar to the early branches of the MCA, although the extent of vascular supply may vary 10 , 11 , 20 , 2426…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation